Intravitreal bevacizumab injection alone or combined with macular photocoagulation compared to macular photocoagulation as primary treatment of diabetic macular edema - Jovanović, Sandra P; Čanadanović, Vladimir; Sabo, Ana; Grgić, Zorka; Mitrović, Milena; Rakić, Dušan (Vojnosanitetski pregled, 2015)
Background/Aim. Within diabetic retinopathy (DR), diabetic macular edema (DME) is one of the leading causes of the loss of visual acuity. The aim of this study was to determine the efficacy of the intravitreal vascular endothelial growth factor (VEGF) inhibitor application alone or combined with macular focal/grid lasephotocoagulation compared with laser treatment alone. Methods. This prospective randomized clinical trial included 72 patients (120 treated eyes) with varying degrees of DR and DME. The DME treatment included intravitreal VEGF inhibitor bevacizumab (Avastin®) application, with and without laser treatment. Bevacizumab (1.25 mg/0.05 mL) was administered intravitreally in 4–6-week intervals. Laser is applied 4–6 weeks after last dose of the drug as a part of combined treatment, or as the primary treatment. Results. The mean reduction in central macular thickness (CMT) for the eyes (n = 31) treated with bevacizumab alone was 162.23 µm, for the eyes (n = 53) treated with combined treatment the mean reduction in CMT was 124.24 µm, both statistically significant at p < 0.001. Laser macular photocolagulation as a part of combined treatment (in 53 eyes) significantly contributed to the CMT reduction, based on the paired t-test results (366.28 vs 323.0 µm at p < 0.05). In our study, the mean visual acuity improvement of 0.161 logMAR was achieved in the group of eyes treated with bevacizumab alone, and 0.093 logMAR in the group with combined treatment, both statistically significant at p < 0.05. The effect of laser photocolagulation alone on visual acuity and CMT was not statistically significant. Conclusion. Treatment with bevacizumab alone or within combined treatment is more effective in treating DME than conventional macular laser treatment alone, both anatomically and functionally.